2022
DOI: 10.1161/atvbaha.122.317682
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial ENPP2 (Ectonucleotide Pyrophosphatase/Phosphodiesterase 2) Increases Atherosclerosis in Female and Male Mice

Abstract: BACKGROUND: Maladapted endothelial cells (ECs) secrete ENPP2 (ectonucleotide pyrophosphatase/phosphodiesterase 2; autotaxin)—a lysophospholipase D that generates lysophosphatidic acids (LPAs). ENPP2 derived from the arterial wall promotes atherogenic monocyte adhesion induced by generating LPAs, such as arachidonoyl-LPA (LPA20:4), from oxidized lipoproteins. Here, we aimed to determine the role of endothelial ENPP2 in the production of LPAs and atherosclerosis. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Although ATX and LPA are associated reportedly with inflammatory vascular diseases like atherosclerosis, 20,28 their involvement in the alteration of endothelium-dependent vasorelaxation has not yet been investigated. In contrast, the disruptive effect of LPC on vasorelaxation is well-documented; 8,10,11 however, to the best of our knowledge, the potential involvement of ATX and LPA in this process has not been addressed previously.…”
Section: Discussionmentioning
confidence: 99%
“…Although ATX and LPA are associated reportedly with inflammatory vascular diseases like atherosclerosis, 20,28 their involvement in the alteration of endothelium-dependent vasorelaxation has not yet been investigated. In contrast, the disruptive effect of LPC on vasorelaxation is well-documented; 8,10,11 however, to the best of our knowledge, the potential involvement of ATX and LPA in this process has not been addressed previously.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to serum ATX, endothelial ATX could play a role in local LPA production and atherosclerotic plaque formation in apoE knockout, hypercholesterolaemic mice [ 118 ]. Inhibition of ATX by pipedimic acid was shown to decrease bovine endothelial monolayer permeability after anoxia-reoxygenation treatment and reduce the permeability of perfused rat mesenteric post-capillary venules after ischemia reperfusion injury [ 119 ] ( Figure 1 and Figure 2 ).…”
Section: Covid-19-associated Changes In Autotaxinmentioning
confidence: 99%
“…Karshovska et al [24 ▪▪ ] reported that a tamoxifen-induced endothelial cell-specific Enpp2 knockout decreased atherosclerosis plaque area, decreased macrophages in lesions, decreased monocyte adhesion, and decreased endothelial expression of C-X-C motif chemokine ligand 1 (CXCL1) in male and female Apoe-/- mice. In vitro , it was shown that Enpp2 mediated mildly oxidized LDL-induced expression of CXCL1 in aortic endothelial cells by generating LPA 20:4, LPA 16:0 and LPA 18:1 [24 ▪▪ ]. Autotaxin was detected on the endothelial surface, and expression of endothelial Enpp2 strongly correlated with plasma levels of LPA16:0, LPA 18:0 and LPA18:1 and aortic plaque size [24 ▪▪ ].…”
Section: Enodthelial Specific Knockout Of Enpp2mentioning
confidence: 99%
“…In vitro , it was shown that Enpp2 mediated mildly oxidized LDL-induced expression of CXCL1 in aortic endothelial cells by generating LPA 20:4, LPA 16:0 and LPA 18:1 [24 ▪▪ ]. Autotaxin was detected on the endothelial surface, and expression of endothelial Enpp2 strongly correlated with plasma levels of LPA16:0, LPA 18:0 and LPA18:1 and aortic plaque size [24 ▪▪ ]. It was concluded that endothelial autotaxin promotes atherosclerosis in both male and female mice due to the generation of LPA20:4, LPA16:0 and LPA18:1 from mildly oxidized lipoproteins located on the endothelial surface [24 ▪▪ ].…”
Section: Enodthelial Specific Knockout Of Enpp2mentioning
confidence: 99%